2022
DOI: 10.1007/s12032-022-01877-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of early breast cancer onset to understand disease phenotypes in African patients

Abstract: Female breast cancer (BC) is the leading cause of cancer-related deaths worldwide with higher mortality rates and early onset in developing countries. The molecular basis of early disease onset is still elusive. We recruited 472 female breast cancer from two sub-Saharan African countries (Cameroon and Congo) between 2007 and 2018 and collected clinical data from these patients. To investigate the molecular drivers of early disease onset, we analyzed publicly available breast cancer molecular data from the canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…In addition, we observed an enrichment of genes associated with Reelin pathway and Neuroactive ligand-receptor interaction in young African patients with breast cancer, which might indicate a crucial role in breast cancer metastases adapting to the brain microenvironment, thus indicating that these patients might be more prone to brain metastasis and disease progression. Previous studies have reported an enrichment of gene sets associated with tumor progression in Young African patients, which included mTOCRC1 and TGFß-signaling ( Tonouo et al, 2022 ). However, our study is the first to propose an enrichment of the Reelin pathway gene sets in young African patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed an enrichment of genes associated with Reelin pathway and Neuroactive ligand-receptor interaction in young African patients with breast cancer, which might indicate a crucial role in breast cancer metastases adapting to the brain microenvironment, thus indicating that these patients might be more prone to brain metastasis and disease progression. Previous studies have reported an enrichment of gene sets associated with tumor progression in Young African patients, which included mTOCRC1 and TGFß-signaling ( Tonouo et al, 2022 ). However, our study is the first to propose an enrichment of the Reelin pathway gene sets in young African patients.…”
Section: Discussionmentioning
confidence: 99%